Looking Through “Rose-Tinted” Glasses: The Influence of Tint on Visual Affective Processing - Schilling, Tim; Sipatchin, Alexandra; Chuang, Lewis; Wahl, Siegfried (Frontiers in Human Neuroscience, 2019)
The use of color-tinted lenses can introduce profound effects into how we process visual information at the early to late stages. Besides mediating harsh lighting conditions, some evidence suggests that color-tinted lenses can influence how humans respond to emotional events. In this study, we systematically evaluated how color-tinted lenses modified our participants’ psychophysiological responses to emotion-inducing images. The participants passively viewed pleasant, neutral or unpleasant images from the International-Affective-Picture-System (IAPS), while wearing none, blue, red, yellow or green tinted-lenses that were controlled for luminance. Established neuroergonomic indices of arousal were measured on the autonomic level, namely Skin-Conductance-Response (SCR) and Heart-Rate-Variability (HRV), and on the cortical level, with EEG event-related potentials (ERP). Phasic SCR responses were significantly enhanced for unpleasant images and both pleasant and unpleasant images induced significantly larger ERP amplitudes of the Late-Positive-Potential (LPP), with pleasant images having the greatest impact. Interestingly, a significant main effect was found for tint. Similar to viewing pleasant images, red-tinted lenses induced the largest LPPs. Taken together, these findings suggest that the autonomic response to affective images is modulated at the cortical level of processing, congruent with the use of red-tinted lenses.